The notebook keeper : a story of kindness from the border - Briseño, Stephen (Random House Studio, 2022)
After traveling to Tijuana, Mexico, Noemi and her mother are denied entry at the border and must find the refugee in charge of the notebook, an unofficial ledger of those waiting to cross into the United States. Includes author's note.